Reforming the road freight transportation system using systems thinking: An investigation of Coronial inquests in Australia. (April 2017) - Newnam, Sharon; Goode, Natassia; Salmon, Paul; Stevenson, Mark
Highlights: Road freight transportation reform should be underpinned by a systems thinking approach. Publicly available Australian Coroner's inquest reports were analysed from the last 10 years. Lack of evidence to suggest an understanding of system-based reform. Systems thinking based data collection and analysis frameworks are urgently required. Abstract: Road freight transport is considered to be one of the most dangerous industries in Australia, accounting for over 30% of all work fatalities. Whilst system reform (i.e., change to policy and practice) is needed, it is not clear what this reform should be, or what approaches should be used to drive it. This article argues that road freight transportation reform should be underpinned by a systems thinking approach. Efforts to understand crash causation should be focused beyond the driver and identify contributing factors at other levels with the road freight system. Accordingly, we present the findings from a study that examined whether Australian Coronial investigations into road freight crashes reflect support appropriate system reform. Content analysis was used to identify the contributing factors and interrelations implicated in the road freight crashes described in publicly available Australian Coroner's inquest reports from the last 10 years (2004–2014; n = 21). The results found evidence to suggest that the Coronial inquests provide some understanding of the complex system of factors influencing road freight transportation crashes in Australia. However, there was a lack of evidence to suggest an understanding of system-based reform based on the identification of reductionist-focused recommendations. It is concluded that researchers and practitioners (ie., government and industry) need to work together to develop prevention efforts focused on system reforms. Systems thinking based data collection and analysis frameworks are urgently required to help develop this understanding in road freight transportation.